The obsolescense of the court, the evolutions of its application in the new civil procedure code and the shortcomings of the law pending the reform - Popa, Cristina Elena (Civil Procedure Review, 2017)
The respect of the equality of rights, and of the non-discrimination liability, involves taking into accout the treatment provided by the law for the ones to which it is applied, throughout the period while its regulations are affective, legal treatment that cannot be different. The present paper brings into debate a very serious problem, the cannot be different. The present paper brings into debate a very serious problem, the settlement of which consists of the analysis of the constitutionality and/or of the shortcomings of the law bt reference to art. 3 of law no. 76/2012 for the enforcement of law no. 134/2010 regarding the Civil procedura code, in the context of the special obsolescence of ther court, considering the provisions of art. 46 comma which had been abusively taken over during the period March 6 1945- December 22. 1989 (by which the suspension cannot last for an unlimited period of time, without the absolescence to operate, according to the rugulations provided by the old Civil procedure code). Ist shall be further checked whether the principle of nonretroactivity pf the civil procedural law - in terms of the obsolescence of the civil action - is compatible with aty. 8 of the CEDO convention which gaurantees the right to an equitable trial, but also if the litigants who are parties to proceedigs to under the old law are somehow discriminated compared to those who are parties obsolescence within 10 years. Results from this study that Romanian law is located on a transition phase. Reform of areas of law become imperative.